Export competition issues after Nairobi: The recent World Trade Organization agreements and their implications for developing countries - Díaz-Bonilla, Eugenio; Hepburn, Jonathan (International Food Policy Research Institute, 2016)
This paper reviews, from the perspective of developing countries, the recent agreement reached at the 10th WTO Ministerial at Nairobi related to export competition, including exports subsidies, food aid, export credits and guarantees, and state trading enterprises (STEs). The legal and economic aspects of the agreement are examined, and the relevance of banning agricultural export subsidies are noted. This eliminates some of the worst-case scenarios, if agricultural world prices continue to soften and the important margin of export subsidies still allowed under the WTO framework was to be used. But given the relatively longer transition period for some relevant products before export subsidies are completely banned, the paper argues for continued monitoring of the potential use of this instrument. The paper also discusses the other components of export competition, looking into the legal and economic aspects. Some suggestions about continuous work on transparency and monitoring of current practices, and further disciplines are also presented.